Determinants of Psychological Disorders Among Pregnant Women in Indonesia: A Cross-sectional Study on The Roles of Social Support, Parity, and Anxiety - Budiarti, Astrida; Hastuti, Puji; Fatimawati, Iis; Sulistyawati, Rahmah (Chakra Brahmanda Lentera Institute, 2025)
Background: Pregnancy involves physical and emotional changes that can impact a woman's psychological well-being. However, few studies have explored the combined influence of social support, parity, and anxiety on psychological disorders among pregnant women in Indonesia. This study aimed to examine the relationship between social support, parity, and anxiety with psychological disorders among pregnant women in Indonesia. Methods: A cross-sectional study was conducted among 114 pregnant women attending antenatal care at East Java, Indonesia, community health centers. Participants were selected using a simple random sampling technique. Inclusion criteria were pregnant women living with their husbands or family members, while those who declined participation were excluded. Data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS), Depression Anxiety Stress Scale-21 (DASS-21, anxiety subscale), and the Antenatal Risk Questionnaire (ANRQ). Data were analyzed using descriptive statistics and Spearman’s rho correlation. This study complied with the STROBE reporting guidelines. Results: Most respondents were aged 24–29 years (43.9%), had senior high school education (75%), were housewives (54.4%), and had moderate family income (46.5%). The results showed that low social support (p = 0.002), being multiparous (p = 0.003), and higher anxiety levels (p = 0.001) were significantly associated with increased psychological disorder risk. Women with low social support or severe anxiety had the highest risk. Multiparous women were more likely to report psychological distress compared to primiparous women. Social support, parity, and anxiety were significant factors associated with psychological disorders during pregnancy. Conclusion: Mental health should be an integral part of antenatal care. These findings underscore the need to integrate mental health screening and family-based support into routine antenatal care to improve maternal psychological well-being.